UPCYCLING CLOTHING ARTICLES: DIRECTIONAL PRACTICE AS ENTREPRENEURIAL SKILL FOR FAMILY SUSTAINABILITY (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
The purpose  of  the  study  was  to  produce  infant  clothing  articles  using fabric  waste  and patchwork technique. Specifically, the study sought to: produce five infant clothing articles using fabric   waste   and  patchwork   technique  for   various   infant   activities   and   assessed   the appropriateness  of  infant  clothing  articles  produced from fabric  waste  using  patchwork technique based on functional, expressive and aesthetic attributes. The study was guided by three hypotheses. The study was undertaken in two phases. The research and development design were adopted for phase I while a descriptive survey design was utilized for phase II of  the study. Purposive sampling technique was used to select 15 judges for the study. infant clothing article assessment  instrument for judges  (ICAAIJ)  was  used  in  phase  two  of  the  study for  data collection. The reliability of the instrument was determined using Cronbach Alpha coefficient which yielded as follows: functional attribute= 0.84, expressive attribute = 0.90 and aesthetic attribute =0 .82.ANOVA were used to test the hypotheses at 0.05 level of significance. Findings revealed that judge’s acceptance was significantly related to aesthetic, expressive and functional attributes of infant clothing articles produced. Among recommendations made were that Schools in Rivers State should set up practical fabric recycling programmes and activities in schools to enlightened  and  encourage  students  on fabric  waste  utilization  and  that  lecturers  in  the Department of Home Economics in tertiary institutions should carry out more practical work on utilization  of fabric  waste for  the  production  of  useful  articles  using  different  clothing construction techniques.